Pengaruh Kualitas Laman, Persepsi Kepercayaan, dan Persepsi Kualitas Produk Terhadap Niat Membeli Secara Online pada Situs Belanja Online Zalora di Denpasar - Hendrayana, I Wayan; Santika, I Wayan (E-Jurnal Manajemen; Vol 4 No 2 (2015), 2015)
The purpose of this study is to determine the effect of page quality, perceived trust, and perceived quality product of Purchase intention to product online at sites online shopping Zalora in Denpasar. Respondent this research were 120 people with the method of data collection using questionnaires. The analysis technique used in this study is the technique of multiple linear regression analysis. Based on the discussion of the variables Page Quality, Perceived Trust and perceived quality product and significant positive effect on Purchase intention to online at sites online shopping Zalora in Denpasar. Keywords: Page Quality, Perceived Trust, Perceived of Product Quality, Purchase Intentions, Online  Shopping
Keywords: Keywords: Page Quality, Perceived Trust, Perceived of Product Quality, Purchase Intentions, Online Shopping